Rwanda Agriculture Finance Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture is critical to Rwanda’s economy and a key sector in Rwanda’s Economic Development and Poverty Reduction Strategy (EDPRS). Agriculture finance is a national priority to achieve transformation of the agriculture sector and greater financial inclusion. Prioritizing agriculture finance has yielded substantial achievements, but farmers’ use of formal financial services remains suboptimal. Demand-side data on the use of financial services by agri-enterprises are not available. The limited depth of the agricultural credit market is also reflected at the macro level. The report identifies several challenges to increasing access to financial services to the agricultural sector. However, Rwanda has key institutional foundations in place to scale up agriculture finance. The report identifies four key opportunities to further develop agriculture finance in Rwanda and recommends policy and institutional actions to realize these opportunities effectively.